Quality indicators in nutrition therapy within the intensive care setting of a Brazilian teaching hospital - Rosa, Teresa Cristina Abranches; Raslan, Mariana; Souza, Albert Schiaveto de; Gielow, Karine de Cássia Freitas (Interações, 2019)
The quality of nutritional therapy was evaluated in an adult intensive care unit in a Brazilian teaching hospital, using ten indicators expressing target quality rates were selected from a list compiled by the Clinical Nutrition Task force of the Brazilian chapter of the International Life Sciences Institute (ILSI-Brasil). It was observed that the use of quality indicators of nutritional therapy allowed the identification of compliance and nonconformity processes, which still need additional adjustments.